Websites as Supplementary Reading Materials: Challenges Faced by Vocational Students - Sri Rejeki; Diah Kristina; Agus Wijayanto (Universitas Hamzanwadi, 2022)
Responding the needs of vocational students to master the English skills once they graduate from vocational college, a group of vocational student used three EFL websites, namely English Club, BBC Learn English and Learn English British Council, for three months as supplementary reading materials. There were twelve students majoring in Accounting Information System from Diploma 3 Program at one of private colleges in Surakarta. This study employed questionnaire and online artefacts to collects the data. It was found that most of the students mentioned technical challenges that they faced when accessing websites as supplementary reading materials. Easy get tired and different level of English comprehension were challenges faced by them. Furthermore, students felt that they do not need to spend much money, could download the materials and able to improve their skills by accessing the websites. It is suggested to conduct further research in the same field with wider respondents and longer period by employing pre, during and post-test before and after using the websites to find out the significant impacts for the students.